Case Report: Diffuse idiopathic skeletal hyperostosis with ossification of the posterior longitudinal ligament in the cervical spine: A rare case with dysphagia and neurological deficit and literature review - Li, Chaoyuan; Luo, Wenqi; Zhang, Hongchao; Zhao, Jianhui; Gu, Rui (Frontiers in Surgery, 2022)
Diffuse idiopathic skeletal hyperostosis (DISH) is characterized by the calcification and ossification of ligaments and tendons. Progressive dysphagia caused by DISH-related anterior cervical osteophytes and deteriorating dysphagia caused by DISH combined with neurological dysfunction resulting from the posterior longitudinal ligament is rare. Patients with progressive dysphagia as the initial symptom often consult a thoracic surgeon. The aim of this review is to highlight this rare condition for spine surgeons via one reported case where a 53-year-old man presented with progressive dysphagia and foreign body sensation in the pharynx, accompanied by a neurological numbness defect in the right upper limb. X-ray imaging and computed tomography confirmed the existence of osteophytes at the anterior edge of the C4–C7 pyramid and ossification of the posterior longitudinal ligament, in which the giant coracoid osteophyte could be seen at the anterior edge of the C4–C5 pyramid. The anterior cervical osteophyte was removed, and decompression and fusion were performed. The symptoms were relieved postoperatively. No recurrence of symptoms was found during the 3-month follow-up. Spine surgeons should consider progressive dysphagia caused by DISH-related osteophytes at the anterior edge of the cervical spine as it is easily misdiagnosed and often missed at the first diagnosis. When combined with OPLL, following cervical osteophyte resection, it is necessary to consider stabilizing the corresponding segments via fusion.